Factors Within the Endoneurial Microenvironment Act to Suppress Tumorigenesis of MPNST - Stratton, Jo Anne; Assinck, Peggy; Sinha, Sarthak; Kumar, Ranjan; Moulson, Aaron; Patrick, Natalya; Raharjo, Eko; Chan, Jennifer A.; Midha, Rajiv; Tetzlaff, Wolfram; Biernaskie, Jeff (Frontiers in Cellular Neuroscience, 2018)
Background: Deciphering avenues to adequately control malignancies in the peripheral nerve will reduce the need for current, largely-ineffective, standards of care which includes the use of invasive, nerve-damaging, resection surgery. By avoiding the need for en bloc resection surgery, the likelihood of retained function or efficient nerve regeneration following the control of tumor growth is greater, which has several implications for long-term health and well-being of cancer survivors. Nerve tumors can arise as malignant peripheral nerve sheath tumors (MPNST) that result in a highly-aggressive form of soft tissue sarcoma. Although the precise cause of MPNST remains unknown, studies suggest that dysregulation of Schwann cells, mediated by the microenvironment, plays a key role in tumor progression. This study aimed to further characterize the role of local microenvironment on tumor progression, with an emphasis on identifying factors within tumor suppressive environments that have potential for therapeutic application. Methods: We created GFP-tagged adult induced tumorigenic Schwann cell lines (iSCs) and transplanted them into various in vivo microenvironments. We used immunohistochemistry to document the response of iSCs and performed proteomics analysis to identify local factors that might modulate divergent iSC behaviors. Results: Following transplant into the skin, spinal cord or epineurial compartment of the nerve, iSCs formed tumors closely resembling MPNST. In contrast, transplantation into the endoneurial compartment of the nerve significantly suppressed iSC proliferation. Proteomics analysis revealed a battery of factors enriched within the endoneurial compartment, of which one growth factor of interest, ciliary neurotrophic factor (CNTF) was capable of preventing iSCs proliferation in vitro. Conclusions: This dataset describes a novel approach for identifying biologically relevant therapeutic targets, such as CNTF, and highlights the complex relationship that tumor cells have with their local microenvironment. This study has significant implications for the development of future therapeutic strategies to fight MPNSTs, and, consequently, improve peripheral nerve regeneration and nerve function.